KLASIFIKASI DATA NASABAH KREDIT PINJAMAN MENGGUNAKAN DATA MINING DENGAN METODE K-MEANS PADA MEGA CENTRAL FINANCE: Active;Data Mining;K-Means;Passive;Repeat Order;Rapid Miner. - Limia Budiarti, Rike; Cendana, Gina (JURNAL AKADEMIKA, 2022)
Mega Central Finance (MCF) Group is a company under CT.Corpora. The Mega Central Finance (MCF) Group company functions as a company engaged in financing and credit, located in Muara Bulian. The purpose of this study using the "K-means" data mining method is to obtain data reports on customers who are entitled to receive loans from the Mega Central Finance (MCF) Group. Clustering includes inputting data from customers who apply for loans, then entering the registration process to enter the customer's name, the calculation process using RapidMiner. It takes several variables used in clustering, namely the variable "Amount of Loans, Term, Income, Number of Pickup Vehicles". The results of clustering obtained three clusters, namely cluster 1 there are 7 active customer data which has a very small number of clusters. Cluster 2 contains 93 passive customer data which has a cluster number with the highest number of customer data from cluster 1 and cluster 3. Cluster 3 contains 50 repeat order customer data which has a moderate number of clusters. Finally, the results from the three clusters above are obtained.